Hydrothermal activity around the Mienhua submarine volcano in the northern margin of the southern Okinawa Trough - Ching-Hui Tsai; Shu-Kun Hsu; Hsiao-Shan Lin; Song-Chuen Chen; Liwen Chen; Chin-Wei Liang; Ching Hsu; Lien-Kai Lin; Yen-Yu Cho (Terrestrial, Atmospheric and Oceanic Sciences)
Abstract Using deep-towed side-scan sonar (SSS) and sub-bottom profiler (SBP) data, we have investigated the hydrothermal activity around the Mienhua submarine volcano (MHV) at the northern margin of the southern Okinawa Trough. Our result reveals widespread acoustic transparent zones (TZs) in the shallow subsurface, which are generally interpreted as porous strata filled with hydrothermal fluid. These acoustic transparent zones exhibit lateral thinning and overpressure characteristics. Because the fluid channels are usually found beneath the thicker part of the transparent zones, a vertical migration of the hydrothermal fluid at depth and a horizontal migration or diffusion of the hydrothermal fluid in shallow high-porosity sediments are suggested. Our SBP profiles indicate multiple fluid channels vertically cutting through sedimentary layers and connecting with the upper TZs. The over-pressured hydrothermal fluid sometimes escapes from the seafloor and forms gas flares in the seawater column. The associated chimney structures (possibly black smokers) at the seafloor can be observed in the SSS imagery. The existence of the fluid channels, TZs, chimney features, and gas flares indicates an active and focused hydrothermal activity. However, the hydrothermal activity is vigorous in the eastern side of MHV. In contrast, the western and southern sides of the MHV display a waning or cessation of the hydrothermal activity, because of few chimney structures, seabed subsidence, and almost no gas flares. The hydrothermal activity in the MHV area reveals a temporal and spatial shift from west to east. By calculating the distribution of the mound-like or chimney structures from the SSS data, we estimate that the possibly hydrothermal mineralization area is approximately 2.2 km2. Our findings provide important insights into a submarine hydrothermal activity that is helpful for potential seabed mining in the MHV area.